Métodos e espécies potenciais para a restauração de áreas degradadas no Parque Estadual Quarta Colônia, RS - Marcuzzo, Suzane Bevilacqua (2012)
Generally, works of public interest, such as the construction of hydroelectric power plants cause changes in ecosystems. Compensation for damage shall be notified by the entrepreneur, through ecological restoration of degraded ecosystem. Thus, the present study was designed to evaluate the evolution of areas in restoration process for a forest remnant more preserved, as well as evaluating methods and potential species, capable of maintaining the functionality of ecosystems. The State Park Quarta Colônia is full protection unit of 1847 hectares, located in the municipality of Agudo and Ibarama, Rio Grande do Sul, established in 2005, as a compensatory measure to the work of the hydroelectric dam of Dona Francisca, Rio Grande do Sul. The work was developed in chapters, where initially, held the definition and characterization of the reference area, establishing parameters for comparison with the areas in process of restoration. The reference area is located near 555.82 m of reclaimed areas, and 615.33 m of another, is composed of secondary forest in middle to advanced stage of succession. The vegetation of the reference area was recorded using 10 x 20 m 12 plots (200 m²) on tracks 100 m apart between sí, and 20 m between plots distributed systematically by topography gradient, being held at the circumference measurement of height peiro (CAP) of all individuals and arboreal with CAP ≥ 15 cm arbustivos. The regeneration was measured in circular sub-plots with radius of 1.78 m (10 m2) in the center of the parcels, and individuals with height ≥ 30 cm and CAP<15 cm. Data analysis was performed by means of the structure and diversity of vegetation and floristic groups, in addition to a canonical correspondence analysis between vegetation and environmental variables, where there was the formation of two groups floristic located according to the excerpts from land use and chemical characteristics. The second chapter deals with two areas in process of restoring deployed for seven years, styling-if A1, an area with restoration model based on successional species, and A2 the same criterion, but with wider spacing. To check the evolution of the process of restoration of the areas were considered attributes of floristic composition and vegetation structure structure, as well as environmental variables involved in ecological processes. The areas A1 and A2 were sampled by 18 plots, 10 x 20 m (200 m2), in each one, where he was observing the diameter, height and canopy coverage of individuals. The natural regeneration has been studied in sub-plots of 2 x 2 m (4 m2), retrieving the collar diameter and height (0.10 to 1.0 m). The environmental variables represented by the enzyme activity in soil, was observed through the collection of 10 samples of soil, in layers of 5 cm and 0 to 5 to 20 cm, in each area. The results showed that, in addition to the floristic composition and vegetation structure, the enzyme activity is a potential sign of the quality of the site, which indicates that the two areas restored retook the succession process, however A1 presents environmental conditions more favourable to development, enabling infer about the need for management, for the development of areas in recovery. The third chapter search information for deploying a restoration model for low-cost conservation unit and surroundings, where was rated a planting model composed of native forest species functionally divided into Group of fill (Enterolobium contortisiliquum, Schinus terebinthifolius Parapiptadenia rigida, Inga, vera, Luehea divaricata, Psidium cattleyanum) and diversity Group (Eugenia uniflora, Allophylus edulis, Cedrela fissilis, Prunus myrtifolia, Jacaranda micrantha, Cupania vernalis Cabralea canjerana,) and, associated with that, there was the influence of the staging area for subsoiling and seeding with legumes Vicia sativa. The experiment was deployed on delineation of blocks blocks in 2 x 2 x 4 trifatorial (method of staging area x Vicia sativa x time). The treatments consisted of: T1-cova planting tree species (fill-GP group and diversity-GD); T2-cova planting tree species (GP and GD) Vicia sativa; T3-subsoiling planting tree species (GP and GD); and T4-subsoiling planting tree species (GP and GD) Vicia sativa. The observed variables (mortality, collar diameter, height and diameter of the Cup) were subjected to analysis of variance and determination of the significance of the main effects of factors and interactions. The comparison of the species was analyzed by Kruskal-Wallis test, and the comparison of averages by Dunn's Test. It was noted that the use of subsoiling was the best method, indifferent to the use of Vicia sativa due its competitiveness with diversity group seedlings. Enterolobium contortisiliquum, Schinus terebinthifolius and Inga vera are indicated to compose the group, while filling, species diversity group, in the circumstance of the experiment, should be introduced after partial coverage of the canopy. Considering the results of this study it was not possible to conclude that the ecological restoration strategies must ensure that pioneering species, secondary and climax are present in abundance and appropriate distribution, but the diversity group deployment should occur with the canopy formed. The areas A1 and A2 are in continuous process of restoration, although it is necessary for handling your position to keep a successional trajectories close to the original ecosystem.